International financial statement analysis - Robinson, Thomas R. (John Wiley & Sons, 2009)
Professional quality information on international financial statement analysis. International Financial Statement Analysis provides an in-depth understanding of the discipline. It helps readers understand the mechanics of the accounting process; comprehend the differences and similarities in income statements, balance sheets, and cash flow statements; assess the implications for securities valuation of any financial statement element or transaction; and become familiar with different financial analysis techniques that provide valuable insight into a company's operations, risk characteristics.
Includes bibliographical references (pages 803-805) and index. - Print version record
Keywords: Financial statements; International business enterprises -- Accounting; Entreprises multinationales; Comptabilité; BUSINESS & ECONOMICS; Accounting; Financial; International business enterprises; Accounting